Curriculum Analysis to Evaluate Sustainable Learning in High School Physics Through AI-Based Learning Media for SDG 9 - Rahmatta Thoriq Lintangesukmanjaya; Wildan Fitroni; Binar Kurnia Prahani; Dwikoranto Dwikoranto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: The objective of this research is to analyze the implementation of the curriculum at SMAN 1 Cerme, Gresik, in order to identify the alignment of learning outcomes with applicable curriculum standards. This study also aims to contribute to achieving the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), which emphasizes inclusive and equitable quality education, and SDG 9 (Industry, Innovation, and Infrastructure), which encourages innovation in educational practices. Method: This research employs a qualitative descriptive method. Primary data were obtained from interviews and decisions issued by KOSP SMAN 1 Cerme, while secondary data were collected through observations and student response questionnaires. Results: The findings reveal that SMAN 1 Cerme applies the K-13 curriculum for grade XII and the Merdeka Curriculum for grades X and XI. The implementation demonstrates the importance of monitoring and evaluation to ensure the curriculum effectively supports the school's vision and mission. Novelty: This research's novelty lies in integrating curriculum analysis with the Sustainable Development Goals framework. By linking curriculum implementation to SDG 4 and SDG 9, this study highlights how curriculum transformation not only supports local educational objectives but also contributes to global efforts to promote quality education and foster innovation in learning infrastructure.